Transnational corporations in private international law: do Kazakhstan and Russia have the potential to take the lead? - Nukusheva, A.; Ilyassova, G.; Kudryavtseva, L.; Shayakhmetova, Zh.; Jantassova, A.; Popova, L. (Entrepreneurship and Sustainability Issues, 2020)
The aim of this paper is to determine role of transnational corporations (TNCs) in a struggle of Kazakhstan and Russia towards leadership. Concepts and hypotheses from available literature on economic globalization, TNCs, their impact on national economies, and innovation-driven development were analyzed. Most Kazakh corporations have low nominal capitals and hold shares, total value of which does not meet minimum requirements for global competition. Kazakhstan and Russia fail to secure mutual benefit of participants in investment relationship, as well as national interests. Foreign investors professionally utilize all the gaps and weaknesses that can be found in the investment law. In this regard, TNCs are the most prepared, as they have substantial resources to create favorable conditions for market presence.
Keywords: transnational corporation; international investing; foreign direct investment; capital concentration; cross-border penetration; mergers and acquisitions; investment policy